Integração entre segurança do trabalho e recursos humanos: a abordagem das normas regulamentadoras - MOREIRA, Kaue Tainan (251, 2024)
A sinergia entre Segurança do Trabalho e Recursos Humanos é fundamental para prevenir ambientes de trabalho seguros, saudáveis e produtivos. A Segurança do Trabalho é uma área multidisciplinar que busca saúde e integridade física dos parceiros interno utilizando as normas regularmente e decretos que fundamentem suas ações, enquanto os Recursos Humanos lidam com a gestão do capital humano no âmbito das organizações Ambas as áreas: com o papel crucial na promoção do bem estar dos colaboradores as áreas trabalham conjuntamente, em resumo, a ligação entre Segurança do Trabalho e Recursos Humanos é essencial para promover ambientes de trabalho seguros, saudáveis e produtivos. Os profissionais de Recursos Humanos desempenham um papel fundamental em todas as etapas, desde o recrutamento e seleção até a gestão de incidentes e a promoção do bem-estar dos colaboradores. Ao trabalhar em conjunto, essas duas áreas podem contribuir significativamente para o sucesso e a sustentabilidade das organizações.

The synergy between Occupational Safety and Human Resources is essential to prevent safe, healthy and productive work environments. Occupational Safety is a multidisciplinary area that seeks health and physical integrity of internal partners using standards regularly and decrees that support its actions, while Human Resources deals with the management of human capital within organizations Both areas: with the role crucial in promoting the well-being of employees, the areas work together, in short, the link between Occupational Safety and Human Resources is essential to promote safe, healthy and productive work environments. Human Resources professionals play a fundamental role at all stages, from recruitment and selection to incident management and promoting employee well-being. When working together, these two areas can significantly contribute to the success and sustainability of organizations.

The synergy between Occupational Safety and Human Resources is essential to prevent safe, healthy and productive work environments. Occupational Safety is a multidisciplinary area that seeks health and physical integrity of internal partners using standards regularly and decrees that support its actions, while Human Resources deals with the management of human capital within organizations Both areas: with the role crucial in promoting the well-being of employees, the areas work together, in short, the link between Occupational Safety and Human Resources is essential to promote safe, healthy and productive work environments. Human Resources professionals play a fundamental role at all stages, from recruitment and selection to incident management and promoting employee well-being. When working together, these two areas can significantly contribute to the success and sustainability of organizations.
Keywords: Segurança do trabalho; Normas de segurança; Recursos humanos; Gestão e Negócios